Didactic aspects about the abilities as learning content. - Luis Alberto Corona Martinez; Mercedes Fonseca Hernández. (Medisur)
This article includes a review aimed at strengthen the theoretical basis of medicine professors regarding the most important didactic aspects related with abilities and its acquisition in the teaching-learning process. In addition to the conceptual analysis, it is important to take into account many psychological and methodological elements that are indispensable to create and develop abilities.